Corresponding ECoG and fMRI category-selective signals in human ventral temporal cortex. (March 2016) - Jacques, Corentin; Witthoft, Nathan; Weiner, Kevin S.; Foster, Brett L.; Rangarajan, Vinitha; Hermes, Dora; Miller, Kai J.; Parvizi, Josef; Grill-Spector, Kalanit
Abstract: Functional magnetic resonance imaging (fMRI) and electrocorticography (ECoG) research have been influential in revealing the functional characteristics of category-selective responses in human ventral temporal cortex (VTC). One important, but unanswered, question is how these two types of measurements might be related with respect to the VTC. Here we examined which components of the ECoG signal correspond to the fMRI response by using a rare opportunity to measure both fMRI and ECoG responses from the same individuals to images of exemplars of various categories including faces, limbs, cars and houses. Our data reveal three key findings. First, we discovered that the coupling between fMRI and ECoG responses is frequency and time dependent. The strongest and most sustained correlation is observed between fMRI and high frequency broadband (HFB) ECoG responses (30–160 hz). In contrast, the correlation between fMRI and ECoG signals in lower frequency bands is temporally transient, where the correlation is initially positive, but then tapers off or becomes negative. Second, we find that the strong and positive correlation between fMRI and ECoG signals in all frequency bands emerges rapidly around 100 ms after stimulus onset, together with the onset of the first stimulus-driven neural signals in VTC. Third, we find that the spatial topology and representational structure of category-selectivity in VTC reflected in ECoG HFB responses mirrors the topology and structure observed with fMRI. These findings of a strong and rapid coupling between fMRI and HFB responses validate fMRI measurements of functional selectivity with recordings of direct neural activity and suggest that fMRI category-selective signals in VTC are associated with feed-forward neural processing. Highlights: We measured ECoG and fMRI responses to visual stimuli in VTC of the same subjects. Topology and distributed pattern of category-selectivity match across ECoG and fMRI. fMRI correlation with ECoG HFB signal is the strongest and most sustained. fMRI correlation with ECoG low frequency signals is temporally transient. ECoG–fMRI correlation emerges at ~100 ms, simultaneous with neural responses in VTC.